2010
DOI: 10.1128/jcm.01157-10
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Mammary Tumor Virus-Like Nucleotide Sequences in Canine and Feline Mammary Tumors

Abstract: Mouse mammary tumor virus (MMTV) has been speculated to be involved in human breast cancer. Companion animals, dogs, and cats with intimate human contacts may contribute to the transmission of MMTV between mouse and human. The aim of this study was to detect MMTV-like nucleotide sequences in canine and feline mammary tumors by nested PCR. Results showed that the presence of MMTV-like env and LTR sequences in canine malignant mammary tumors was 3.49% (3/86) and 18.60% (16/86), respectively. For feline malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
(25 reference statements)
4
32
1
Order By: Relevance
“…For the detection of endogenous Djungarian hamster provirus DNA (MRS-Ps) derived from mouse mammary tumour virus (MMTV) the DNA isolates were analysed by amplification of DNA fragments using the poly- Table 2. Amplification and sequencing primers for detection of endogenous MMTV DNA (Hsu et al 2010 GGA-TGG-CGA-ACA-GAC-ACA-AAC-AC Figure 7. Carcinoma in situ (blue arrows) and initial phase of invasion of carcinoma cells into adjacent connective tissue (red arrows); staining with HE merase chain reaction (PCR).…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For the detection of endogenous Djungarian hamster provirus DNA (MRS-Ps) derived from mouse mammary tumour virus (MMTV) the DNA isolates were analysed by amplification of DNA fragments using the poly- Table 2. Amplification and sequencing primers for detection of endogenous MMTV DNA (Hsu et al 2010 GGA-TGG-CGA-ACA-GAC-ACA-AAC-AC Figure 7. Carcinoma in situ (blue arrows) and initial phase of invasion of carcinoma cells into adjacent connective tissue (red arrows); staining with HE merase chain reaction (PCR).…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…Carcinoma in situ (blue arrows) and initial phase of invasion of carcinoma cells into adjacent connective tissue (red arrows); staining with HE merase chain reaction (PCR). According to Hsu et al (2010) a primer set of eight specific amplification and sequencing primers for the detection of mouse mammary virus-like nucleotide sequences were used (Table 2). The PCR reactions were performed in a 50 µl amplification mix using the PPP master mix (TopBio, Prague) with different primer combinations.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…Hsu et al (8) reported the presence of MMTV-like nucleotide sequences in canine and feline mammary tumours. They used the nested PCR method in CMT tissues and detected 3.49% of MMTV-like env and LTR sequences.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, only Hsu et al (8) have investigated MMTV-like sequences in canine and feline mammary tumours and normal mammary tissues (not in cell lines), but EBV, HPV, and PV have never been investigated as aetiological factors. Thus, the aim of this study was to evaluate the possible pathogenic properties of these viruses in dog mammary tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggested the involvement of MMTV in neoplastic mammary glands of cats and dogs. Companion animals might contribute to the transmission of MMTV between mouse and man [51]. MMTV-like virus DNA has been detected in several human cancers including breast, liver, ovarian, prostate, endometrial, and skin malignancies [52,53].…”
Section: Retroviruses-related Cancermentioning
confidence: 99%